An Investigation On The High-Mg-Content Slag In linchuan Nickel Flash Smelting Furnace - Wang Zhi (The Minerals, Metals and Materials Society, 2003)
High-Mg-content concentrates are usually treated in Jinchuan flash smelting Furnace. Because the viscosities of high-Mg-content slag is very high, the operation of flash smelting becomes very difficult. To solve this problem, the viscosities of the semi-synthesized FeO-MgO-SiO2 slag of different compositions were measured. The results showed that when in the slag the weight percentage of MgO [w(MgO)] is 6-10%, the ratio of the weight percentage of iron to that of Si02, w(Fe)/w(Si02) is 1.1-1.4 and the temperatures are within 1473-1773K, the slag viscosities increased with the increase of W(MgO) and w(Fe)/w(SiO,). When w(Mgo)<6%, the smelting temperature should be controlled at I 300°C in order to to keep the smooth operation. When w(MgO)>10%, the temperature should be kept above I 633K. When the content of MgO is higher, a lower viscosity slag can be produced by decreasing the ratio of w(Fe)/w(SiO,). The appropriate ratio of w(Fe)/w(SiO,) for Jinchuan flash smelting furnace is about 1.2.